2021
DOI: 10.21037/jtd-21-1909
|View full text |Cite
|
Sign up to set email alerts
|

3'-daidzein sulfonate protects myocardial cells from hypoxic-ischemic injury via the NRF2/HO-1 signaling pathway

Abstract: Background: Myocardial infarction (MI) has a high mortality and disability rate and greatly affects human health. This study sought to explore the therapeutic effect and molecular mechanism of 3'-daidzein sulfonate (DSS) on MI. Methods: A rat MI model was established and low and high doses of DSS were administered to the rats. An in vitro oxygen glucose deprivation model was used to verify the treatment role and mechanism of DSS. The establishment of the rat MI model was confirmed by electrocardiogram. The tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…9,10 The advantages of Chinese traditional medicine in treatment of VD increasingly highlight, which has rich resources, multiple targets, and the small side effects. [11][12][13] Dendrobium nobile polysaccharides (DNP) is a perennial epiphytic herb of dendrobium of orchidaceae. Its main medicinal components are polysaccharide and dendrobium alkaloid.…”
Section: Recently Found That Subcortical Ischemic Vd Patients Have Ab...mentioning
confidence: 99%
“…9,10 The advantages of Chinese traditional medicine in treatment of VD increasingly highlight, which has rich resources, multiple targets, and the small side effects. [11][12][13] Dendrobium nobile polysaccharides (DNP) is a perennial epiphytic herb of dendrobium of orchidaceae. Its main medicinal components are polysaccharide and dendrobium alkaloid.…”
Section: Recently Found That Subcortical Ischemic Vd Patients Have Ab...mentioning
confidence: 99%
“…Oxidative stress, an imbalance between production of oxidants and antioxidant defenses, participates in the occurrences and progressions of many diseases ( 1 ). Nuclear factor erythroid 2-related factor 2 (Nrf2) is one of the most important endogenous anti-oxidative stress pathways, which has been demonstrated to involve in modulating oxidative stress for maintaining body health, like cardioprotection ( 2 ), neuroprotection ( 3 ), anti-aging ( 4 ), gastrointestinal protection ( 5 ), and kidney protection ( 6 ). As shown in Figure 1 ( 7 , 8 ), under basal conditions, Nrf2 binds to Kelch-like epichlorohydrin-associated protein-1 (Keap1) in the cytoplasm through Cul3 ubiquitin ligase containing E3 to maintain cell homeostasis.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have confirmed that the nuclear factor E2-related factor 2 (Nrf2)/antioxidant response element (ARE) signaling pathway has a vital role in antagonizing chronic cerebral hypoperfusion injury 6 . Oxidative stress oxidizes the active cysteine residues of Kelch-like-ECH associated protein 1 (Keap1), leading to its inactivation and dissociation from Nrf2 protein 7 , 8 . Nrf2 remains stable and transfers into the nucleus, where it combines with smaf of the nucleus to form the Nrf2-Smaf complex, and binds with ARE in a specific sequence 9 .…”
Section: Introductionmentioning
confidence: 99%